Analysis of Rubberized Concrete Deck Slab for different Bridge Structures as Per IRC Loadings - Aditya, K.; Girepunje, Prerna; Singh, Yogesh (International Journal of Scientific Research in Civil Engineering, 2019)
Bridge is an important structure required for the transportation network. Now a day with the fast innovation in technology the conventional bridges have been replaced by the cost effective structured system. For analysis and design of these bridges the most efficient methods are available. Different methods which can be used for analysis and design are AASHTO, Finite element method, Grillage and Finite strip method. In this research work the finite element method is used for the analysis of three different type of bridges i.e. cable stayed, cable suspension and deck slab bridge of constant width and length is considered.  In this study analyze different bridge sections for same loading conditions and sections. The loading class considered is CLASS 70R from IRC 006-2014. A Finite Element model is formulated for this study using Staad beava software package. This model is then analyzed, for parameters like deflection, stress under the influence of moving vehicle load also to discuss the cost effectiveness of each type of bridge.  The basis aim for this study is to give the best output for implementation of these results in future working conditions. In this study it is concluded that cable suspension bridge is comparatively more stable whereas cable stayed bridge is economical of all the types of bridge considered and deck slab bridge shows worst results overall.
Keywords: Staad Beava; Irc; Vehicle; Bridge; Stresses; Deflection; Rubberized Concrete